Automated identification of pathways from quantitative genetic interaction data - Alexis Battle; Martin C Jonikas; Peter Walter; Jonathan S Weissman; Daphne Koller (Molecular Systems Biology)
Abstract High‐throughput quantitative genetic interaction (GI) measurements provide detailed information regarding the structure of the underlying biological pathways by reporting on functional dependencies between genes. However, the analytical tools for fully exploiting such information lag behind the ability to collect these data. We present a novel Bayesian learning method that uses quantitative phenotypes of double knockout organisms to automatically reconstruct detailed pathway structures. We applied our method to a recent data set that measures GIs for endoplasmic reticulum (ER) genes, using the unfolded protein response as a quantitative phenotype. The results provided reconstructions of known functional pathways including N‐linked glycosylation and ER‐associated protein degradation. It also contained novel relationships, such as the placement of SGT2 in the tail‐anchored biogenesis pathway, a finding that we experimentally validated. Our approach should be readily applicable to the next generation of quantitative GI data sets, as assays become available for additional phenotypes and eventually higher‐level organisms.